PERAN CREATIVE PRODUCTION, PUBLICATION & DOCUMENTATION, DAN VIDEO EDITOR DALAM PELAKSANAAN STRATEGI BRAND COMMUNICATION UNTUK MENINGKATKAN BRAND AWARENESS DAN BRAND ENGAGEMENT MAMI AYAM POP MELALUI KAMPANYE “FLAVOR AND TUNES POP” - Nasya Saufika; Nurul Hasfi (Interaksi Online, 2026)
The low level of brand awareness of Mami Ayam Pop in Semarang City, indicated by only 23.3% of 202 respondents recognizing the brand, highlights the need for an effective brand communication strategy to increase brand exposure and audience engagement. This study aims to increase Mami Ayam Pop's brand awareness to 65% and enhance brand engagement through the Flavor and Tunes Pop campaign, which integrates digital communication on Instagram and TikTok with brand activation activities, including Vote Your Iftar Flavor, Ramadhan Satnight Tunes, and POP Bite Reaction. In implementing the campaign, Creative Production was responsible for designing visual communication materials, Publication & Documentation managed social media publications and documented campaign activities, while the Video Editor produced audiovisual content to support digital brand communication. This study employed the AISAS (Attention, Interest, Search, Action, Share) model, with data collected through pre-test and post-test surveys, social media analysis, campaign documentation, and evaluation based on Key Performance Indicators (KPIs). The results showed that the campaign successfully increased Mami Ayam Pop's brand awareness to 65%, increased Instagram followers from 286 to 607 accounts and TikTok followers from 169 to 335 accounts, and improved audience engagement through digital content and brand activation activities. These findings indicate that an integrated brand communication strategy effectively enhances both brand awareness and brand engagement for Mami Ayam Pop.